If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -5) = 6 Reorder the terms: 7(-5 + x) = 6 (-5 * 7 + x * 7) = 6 (-35 + 7x) = 6 Solving -35 + 7x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 7x = 6 + 35 Combine like terms: -35 + 35 = 0 0 + 7x = 6 + 35 7x = 6 + 35 Combine like terms: 6 + 35 = 41 7x = 41 Divide each side by '7'. x = 5.857142857 Simplifying x = 5.857142857
| H(t)=-16t^2+80t+9 | | 66.4mg= | | 2(x-100)+x+3(x-80)=2680 | | 6611.584=2*3.14*r*r+2*3.14*r*61.2 | | 1/3*x+2/6=5*x-2/3 | | 5-0.50x=12 | | x+72+35=180 | | 72+35=180 | | 10-2s=12r+2s | | f(x)=(x-4)(4-x) | | -4(-4+2v)=-20+v | | 3k^2+12k-29=7 | | 1/3x+2/6=5x-2/3 | | (7x+33)=(9x+7) | | 9=2r-5 | | 2x-29=93 | | 23x+5x=2x | | -4(-2x+2)+8x=-(5x+7) | | X-47=12 | | X+3=3+2(2+3x)-5x | | x+x-30=180 | | 6(6x-11)=54x | | b=60+(15+7) | | -5d=20 | | x-30=180 | | (8x-4)+(10x+6)= | | 5x-3=-3x-1 | | (X-7)+12=20 | | 7a-18=-3(-3+3)+7a | | x+15=4x-36 | | -40=b-51 | | H=7+27t-16t^2 |